Pengaruh Literasi Media terhadap Kemampuan Mahasiswa Mengenal Pernyataan Opini Pada Teks Berita Editorial Kasus Korupsi di Media Massa Baru - Nabila Hanna Savhira; Endang Erawan; Kheyene Molekandella Boer (IQTIDA : Journal of Da'wah and Communication, 2022)
This study aims to determine the effect of new media literacy and the ability to recognize opinions in editorial news texts in new mass media. This study used a quantitative research method by distributing questionnaires to 98 students at Mulawarman University. In this study it was found that the media literacy variable had a significant effect on the ability to recognize opinions. This is evidenced by the results of research using a simple linear regression test. First, the significant results must be less than 0.05, in this study sig. is 0.017 and the second, from the results of t count must be greater than t table, namely 2.433 > 1.984. Because of the results of this study, it was concluded that there is an effect of media literacy on the ability to recognize opinions in editorial news texts in new mass media.